The Influence of Promotion and Brand Trust on Purchase Intention of GLAZE Brand Jam Products in Modern Trade Channels in Tangerang City, Indonesia - Anggraini, Rr Renny; Hermawan, Hengki; Amirudin, A. (Golden Ratio of Data in Summary, 2025)
This study aims to analyze the influence of promotion and brand trust on the purchase intention of Glaze jam products marketed through modern trade channels in Tangerang City. The increasing competition in the food additive industry requires PT. Colatta, as the producer of Glaze, is to optimize its marketing strategy. However, the declining sales trend in recent months indicates that the implemented promotional strategy has not effectively attracted consumer interest. Additionally, brand trust is also a crucial factor in purchasing decisions. This study employs a quantitative approach using a survey method and multiple regression analysis. The population of this research consists of consumers who purchase Glaze jam products in modern trade channels in Tangerang City, while the sample is selected using purposive sampling techniques. Data was collected through questionnaires distributed to respondents who met the research criteria. The analysis results show that both promotion and brand trust have a significant influence on purchase intention. Therefore, PT. Colatta needs to enhance its digital marketing strategy, strengthen its brand image, and expand its distribution reach to compete effectively in a highly competitive market.